The Management of Giant Cell Arteritis (GCA) Overlapping with Sjogren Syndrome : A Case Report (Indian Journal of Forensic Medicine & Toxicology, 2022)
Giant cell arteritis (GCA) is an autoimmune vasculitis involving large and medium arteries. GCA israrely associated with autoimmune diseases, such as Sjögren’s syndrome. Glucocorticoids (GC) arethe cornerstone of the treatment of GCA as they are very effective but are often given for 1 year toavoid relapses. Here we report a rare case of GCA overlapping with Sjögren’s syndrome along with themanagement.
Keywords: Giant Cell Arteritis, Management, Sjogren Syndrome